Nanoparticles for radiation therapy enhancement : investigation of radiosensitization induced by gold and iron oxide nanoparticles in glioblastoma cells exposed to photon and proton beams - Guerra, Danieli Born (2021)
Radiotherapy (RT) is one of the most effective and widely used techniques for cancer treatment. Despite the great development of this technique, considerable efforts still need to be made to improve its efficacy and to maximize the differential response between tumor and healthy tissues. The use of nanomaterials as treatment enhancers hold great promises, potentially allowing the reduction of the delivered radiation dose. Recent studies have indicated that high atomic number nanoparticles show enhancement effects; however, with large variability between experiments and radiation type. Moreover, the underlying mechanisms of action are not well understood. Therefore, in this work we sought to improve the mechanistic knowledge about the radiosensitizing effect of metal-based nanoparticles, more specifically gold and iron oxide nanoparticles, in human gliobastoma cells irradiated with different radiation qualities. To further understand the impact of introducing NPs into cells exposed to radiation, five different variables were considered, i) NP material, ii) coating iii) treatment concentration, iv) cell type, and v) radiation quality. Findings from this work show the potential of using metal-based nanoparticles as radiosensitizers, relating the possible mechanisms involved in the radioenhancement observed.